The Causal Effect of Tax Planning on Firms’ Performance of Listed Companies in Thailand - Thanjunpong, Sathaya; Dechsir, Patyot (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2018)
This paper aims to examine the causal effect of tax planning on firms’ performance of listed companies on the Stock Exchange of Thailand exclude listed firms on financial sectors. The sample size consists of 873 firm-years which based on the study period between 2014-2016. Tax planning was measured by the effective tax rate (ETR). The firms’ performance was measured by market performance measure, Tobin’s Q, and accounting performance was measured by return on equity (ROE), return on sales (ROS) and earnings per share (EPS). The correlation analysis and multiple regression analysis were used for data analysis. The results indicated that tax planning had the negative effects on firm value measure (Tobin’s Q) while it had the posittive effects on accounting performance